Nature - Chimpanzees : an unnatural history [videorecording (DVD)]. (Questar, 2007)
The treatment of chimpanzees in America over the last half-century has been surprisingly unkind for our next of kin in the animal world. Meet the rescuers at sancturaries like Fauna Foundation and Save the Chimp who are determined to help them.